Reversible microballoon system for handling bioanalytical assays on centrifugal microfluidic platform / Mohammad Mahdi Aeinehvand - Mohammad Mahdi, Aeinehvand (2016)

(untitled)
The unidirectional nature of centripetal flow, the predominant laminar flow in microfluidic systems, and the unreliability of the capillary valves are three main limitations exist in centrifugal microfluidics. This thesis presents the development of reversible microballoon pump, mixer and valve that enhance the control over the manipulation of liquids in bioanalytical assay on centrifugal microfluidic platforms. The high elasticity of the microballoon allows for an efficient conversion of centrifugally and externally induced forces to pumping, mixing and valving forces. The first liquid handling element presented in this thesis is a microballoon pump that relies on elastic energy stored in a latex membrane. It operates at low rotational speeds (< 1500 rpm) and pumps various liquid volumes towards the centre of the CD. The second presented liquid handling element is a microballoon mixer that operates by the expansion and relaxation of the membrane to provide for a consistent periodical 3D reciprocating flow. The third presented microballoon liquid handling element is a reversible thermo-pneumatic valve (RTPV) that seals or reopens an inlet when a trapped air volume is heated or cooled, respectively. It employs the deflection of a latex membrane to control liquid flow and prevent evaporation of reagents over a wide range of spinning speeds (up to 6000 rpm) and temperatures (up to the operational temperature of the disk materials), respectively. To illustrate their practicality in real life applications, microballoon pump, mixer, and valves are used for the actuation of a siphon channel, biosensing enhancement of dengue virus, and controlling fluid flow in a continuous liquid circulation process, respectively. Finally, an array of RTPVs and a microballoon pump/mixer are imbedded in a microfluidic cartridge to automate a lab protocol required for the multiplexing of temperature-controlled assays. As a pilot study, the cartridge is used for the conversion of multiple dengue virus RNA to cDNA, and reused for the preparation of multiple separated PCR reaction mixtures.